The Role of Reading and Listening Concentration Levels and Learning Style on Vocabulary Acquisition during Online Learning - Isfauzi Hadi Nugroho; Itot Bian Raharjo (Journal on Education, 2025)
This study aims to determine the effect of reading and listening concentration level on students’ ability to recall vocabulary in EFL online classroom based on their learning styles. The research subjects were 142 junior high school students of grade 8 in Kediri Regency, East Java Province, Indonesia that consisted of 45 boys and 97 girls. The participants were asked to read the English vocabulary presented on the power point on the screen and listen to the teacher's explanation regarding the meaning of the words through Google Meet. The participants were divided based on the results of the learning styles survey into three groups, i.e. the visual, auditory, and kinesthetic group. The questionnaire regarding concentration was used to determine the level of concentration in reading and listening during online language learning. The results showed that there are significant differences in the ability to remember English vocabulary between the three groups of learning styles with different level of reading and listening concentration.